2024
DOI: 10.1055/a-2318-1880
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Hydrogen-rich Gas before Acute Exercise Alleviates Exercise Fatigue: A Randomized Crossover Study

Gengxin Dong,
Jianxin Wu,
Yinglu Hong
et al.

Abstract: Hydrogen, as an antioxidant, may have the potential to mitigate fatigue and improve selected oxidative stress markers induced by strenuous exercise. This study focused on previously unexplored approach of pre-exercise inhalation of hydrogen-rich gas (HRG). Twenty-four healthy adult men first completed prelaboratories to determine maximum cycling power (Wmax) and maximum cycling time (Tmax). Then they were subjected to ride Tmax at 80% Wmax on cycle ergometers after inhaled HRG or placebo gas (air) for 60-minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Five studies (34,51,53,56,64) showed that H 2 can significantly improve BLA as compared to the placebo, while another eight publications (nine studies) (23, 25, 26, 29-31, 33, 55) showed opposite results that H 2 cannot significantly improve BLA (Table 1). The pooled ES of BLA was small and significant (SMD = −0.37, 95% CI −0.60 to −0.15, p = 0.001, Supplementary Figure S3), with low heterogeneity (I 2 = 22.0%, p = 0.215).…”
Section: Blamentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies (34,51,53,56,64) showed that H 2 can significantly improve BLA as compared to the placebo, while another eight publications (nine studies) (23, 25, 26, 29-31, 33, 55) showed opposite results that H 2 cannot significantly improve BLA (Table 1). The pooled ES of BLA was small and significant (SMD = −0.37, 95% CI −0.60 to −0.15, p = 0.001, Supplementary Figure S3), with low heterogeneity (I 2 = 22.0%, p = 0.215).…”
Section: Blamentioning
confidence: 99%
“…Four studies (28,56,62,64) showed that H 2 can significantly reduce RPE score as compared to the placebo, while another eight publications (nine studies) (23, 25,26,29,34,55,58,63) showed that H 2 cannot significantly reduce RPE score (Table 1). The pooled ES of the RPE score was small and significant (SMD = −0.37, 95% CI −0.65…”
Section: Rpementioning
confidence: 99%
See 3 more Smart Citations